Evaluation of Clinical Implications of Renal Vessel Morphology during Renal Surgeries - Motasim Billah, Abbas Ali Raza, Ahmad Farzad Qureshi, Ammara Ghafoor, Sabeen Akhtar (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: Aim of this research to examine renal vessels and their morphologies as well as their clinical consequences during renal surgery. Study Design: Cross-sectional study Place and Duration: Anatomy department of Bacha Khan Medical Complex, Mardan and Multan Medical & Dental College Multan during the period from April 2022 to September 2022. Methods: There were 90 cases of both genders presented in this study. Included patients were aged between 20-80 years. With suspected abdominal diseases, patients were referred for abdominal CECT examinations. In contrast-enhanced MDCT images of the Abdomen, the renal arteries were examined for their normal structure and any abnormalities. SPSS 21.0 was used to analyze complete data. Results: Males were higher in numbers 61 (67.8%) than females. Mean age of the patients was 51.3±8.43 years and mean BMI 22.4±8.42 kg/m2. We found frequency of anatomical variations of the renal vessel in 62 (68.9%) cases. Frequency of variations of the renal artery was 47 (52.2%). Among 47 cases, supplementary renal artery was found in 41 (45.6%) cases. Early bifurcation of renal artery in 15 (16.7%). In 11 patients on the right side, 12 patients on the left side, and 3 individuals on both sides, an earlier branching of the renal artery was found. The right side was more often affected by renal vein variations, with 25 (278%) patients having late renal vein confluence and 6 (6.7%) patients having additional renal veins. Patients with late renal vein confluence (3.3%) and retroaortic vein (3.3%) were seen on the left side. Conclusion: Our findings in this research show renal artery alterations are common. Endovascular, laparoscopic, and urological procedures benefit from morphological examination of the renal vessels. Keywords: Abdominal disease, Renal Artery, Conventional Angiography, Anatomical Variations